Deskripsi Kemampuan Pemecahan Masalah Matematis pada Soal Cerita Berdasarkan Tipe Kepribadian Ekstrovert-Introvert Siswa SMP Negeri 6 Rembang - Akhmad Jazuli; Muhimmatul Lathifah (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2018)
This study aims to describe the ability of mathematical problem solving in solving story problems in terms of the extrovert introvert personality types of SMP N 6 Rembang students on a two-variable linear equation system. This research is a qualitative descriptive study. The subjects in this study were students of class VIIIB SMP N 6 Rembang. Selection of Respondents used a purposive sampling technique consisting of three students for each personality type. Data collection techniques using questionnaires, tests, interviews and documentation. Data analysis techniques with data presentation steps, data reduction and conclusions. The results showed that the problem-solving ability for (1) extroverted students: were able to understand the problem and were able to explain again in their own language, were able to draw up a problem-solving plan, were able to carry out calculations and writing very neatly, were able to check the results obtained, ( 2) introverted students: have been able to understand the problem but have not been able to explain again with their own language, have been able to draw up a problem solving plan and are able to do calculations even though the writing is still messy, in general do not re-check the answers he has obtained.